Historical Simulations With HadGEM3‐GC3.1 for CMIP6. (3rd June 2020) - Andrews, Martin B.; Ridley, Jeff K.; Wood, Richard A.; Andrews, Timothy; Blockley, Edward W.; Booth, Ben; Burke, Eleanor; Dittus, Andrea J.; Florek, Piotr; Gray, Lesley J.; Haddad, Stephen; Hardiman, Steven C.; et al.
Abstract: We describe and evaluate historical simulations which use the third Hadley Centre Global Environment Model in the Global Coupled configuration 3.1 (HadGEM3‐GC3.1) model and which form part of the UK's contribution to the sixth Coupled Model Intercomparison Project, CMIP6. These simulations, run at two resolutions, respond to historically evolving forcings such as greenhouse gases, aerosols, solar irradiance, volcanic aerosols, land use, and ozone concentrations. We assess the response of the simulations to these historical forcings and compare against the observational record. This includes the evolution of global mean surface temperature, ocean heat content, sea ice extent, ice sheet mass balance, permafrost extent, snow cover, North Atlantic sea surface temperature and circulation, and decadal precipitation. We find that the simulated time evolution of global mean surface temperature broadly follows the observed record but with important quantitative differences which we find are most likely attributable to strong effective radiative forcing from anthropogenic aerosols and a weak pattern of sea surface temperature response in the low to middle latitudes to volcanic eruptions. We also find evidence that anthropogenic aerosol forcings play a role in driving the Atlantic Multidecadal Variability and the Atlantic Meridional Overturning Circulation, which are key features of the North Atlantic ocean. Overall, the model historical simulations show many features in common with the observed record over the period 1850–2014 and so provide a basis for future in‐depth study of recent climate change. Plain Language Summary: Historical simulations, which successfully reproduce features of the observed climate from the end of the preindustrial period to the near‐present day, contribute to our understanding of the underlying mechanisms that drive or influence climate variability and climate change. The historical simulations described in this paper use the third Hadley Centre Global Environment Model in the Global Coupled configuration 3.1 model. These simulations form part of the UK's contribution to the sixth Coupled Model Intercomparison Project. We assess various aspects of the historical climate system in our simulations against observations. This includes the evolution of global mean surface temperature, ocean heat content, sea ice extent, ice sheet mass balance, permafrost extent, snow cover, North Atlantic sea surface temperature and circulation, and decadal precipitation. The key findings include (a) that the model global mean surface temperature broadly follows the observed record, with a few quantitative differences, and (b) that the ocean circulation and sea surface temperatures of the North Atlantic are likely influenced by historical forcings. In general, the simulations respond to historically evolving influences in a similar manner to the observed world. Therefore, these simulations contribute, as part of the wider CMIP6 multimodel effort, to the understanding of the causes of observed climate change since 1850. Key Points: We describe and evaluate the UK's CMIP6 historical simulations We identify drivers of the modeled global temperature evolution and compare with the observed record We find that anthropogenic aerosol forcings influence the simulation of North Atlantic ocean variability